Factors of Success and Failure in Second Language Learning - Anita Anita (JURNAL ARBITRER, 2013)
This study aims to examine and elaborate the factors that contribute to the success and failure of English speakers as the second language in the pursuit of this language in three aspects of the language: fluency, language structure and pronunciation. Data for this study was obtained by conducting semi structured interviews with two students at Victoria University in Wellington, New Zealand. Qualitative data analysis shows that factors such as second language learning in the pre-trial period, in the second language environment, exposure to the second language, the ability to acculturate, the motivation and the learning strategies impact on the mastery of the languages in the three areas mentioned above. Data analysis also shows that the existence and absence of such factors in the second language learning period significantly affect the mastery of language in the three areas.